Frequency of temporomandibular joint osteoarthritis and related symptoms in a hand osteoarthritis cohort. Issue 5 (May 2017) - Abrahamsson, AK.; Kristensen, M.; Arvidsson, L.Z.; Kvien, T.K.; Larheim, T.A.; Haugen, I.K.
Summary: Objective: The prevalence of osteoarthritis (OA) in the temporomandibular joints (TMJs) in hand OA patients is largely unknown. Our aims were to explore (1) The frequency of TMJ-related symptoms and clinical findings; (2) The TMJ OA frequency defined by cone beam computed tomography (CBCT); and (3) The relationship between TMJ-related symptoms/clinical findings and CBCT-defined TMJ OA, in a hand OA cohort. Methods: We calculated the frequencies of TMJ-related symptoms, clinical findings and diagnosis of TMJ OA by CBCT and clinical examination in 54 patients from the Oslo hand OA cohort (88% women, mean (range) age 71 (61–83) years). Participants with and without CBCT-defined TMJ OA were compared for differences in proportions (95% confidence interval (CI)) of symptoms and clinical findings. Sensitivity and specificity of the clinical TMJ OA diagnosis were calculated using CBCT as reference. Results: Self-reported symptoms and clinical findings were found in 24 (44%) and 50 (93%) individuals (93%), respectively, whereas 7 (13%) had sought healthcare. Individuals with CBCT-defined TMJ OA ( n  = 36, 67%) reported statistically significantly more pain at mouth opening (22%, 95% CI 4–40%), clicking (33%, 95% CI 14–52%) and crepitus (25%, 95% CI 4–46%). By clinical examination, only crepitus was more common in TMJ OA (33%, 95% CI 29–77%). Clinical diagnosis demonstrated low sensitivity (0.42) and high specificity (0.93). Conclusions: CBCT-defined TMJ OA was common in hand OA patients, suggesting that TMJ OA may be part of generalized OA. Few had sought healthcare, despite high burden of TMJ-related symptoms/findings. Clinical examination underestimated TMJ OA frequency.